A framework for modelling soil structure dynamics induced by biological activity. (23rd August 2020) - Meurer, Katharina; Barron, Jennie; Chenu, Claire; Coucheney, Elsa; Fielding, Matthew; Hallett, Paul; Herrmann, Anke M.; Keller, Thomas; Koestel, John; Larsbo, Mats; Lewan, Elisabet; Or, Dani; et al.
Abstract: Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil. Abstract : This photograph, depicting ant bioturbation, was taken at the compaction recovery experiment at Agroscope, Zurich, Switzerland. Together with other biological processes, faunal bioturbation profoundly influences soil structure and thus soil physical and hydraulic properties, hydrological processes and plant growth. The parsimonious model concept developed in this paper, which is designed to be compatible with profile‐scale soil–crop models, allows simulation of the effects of biological agents (e.g. plant roots and soil‐living organisms) on soil structure dynamics.